Serum Progesterone, Oestradiol-17β, FSH and LH levels in Anestrus Surti buffaloes treated with Ovsynch alone and in combination with PRID - Savani, HR; Khasatiya, CT; Saxena, Swati; Patel, SB; Singh, VK (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
This study was carried out on 18 postpartum anestrus Surti buffaloes, divided into three equal groups (6 in each) to evaluate the serum progesterone, oestradiol-17β, FSH and LH concentrations (by ELISA) before, during and after Ovsynch and Ovsynch + PRID protocols. Six anestrus buffaloes each were treated with standard Ovsynch protocol (T1) and Ovsynch along with PRID (Progesterone releasing intravaginal device) protocol (T2) with fixed-time AI (FTAI). Six anestrus buffaloes were kept as untreated control (T3). Blood samples were obtained from the animals on day 0 (before treatment), day 4 (during treatment), day 8 (after PGF2α injection), day of induced estrus/FTAI and day 18 post-AI (after treatment). The mean serum progesterone level on day 4 was significantly (p
Keywords: Surti Buffalo; Progesterone; Oestradiol-17β; FSH and LH profile; Ovsynch and Ovsynch PRID protocol